Cell Anatomy Study of MyoSatellite Cells after Breast Cancer Chemotherapy - صارم بسام; عبد الجواد قبيلي; علي داود (Latakia University Journal -Medical Sciences Series, 2023)
Study involved tow randomized groups with invasive breast cancer Stage IIIA. The control group included 31 samples before chemotherapy while the cases (oppose) one included 49 patients after AC (Doxorubicin plus Cyclophosphamide) is finished. Skeletal muscle biopsies performed using needle biopsy. Electron microscope study performed at the Atomic Energy Agency. Results revealed significant nucleus anomalies in 73.46% of MyoSatellite cells of cases samples whereas the rate was 22.59% for control ones.